Η πρωτοβουλίααριστείας στα γερμανικά πανεπιστήμια : το πανεπιστημιακό όραμα του μέλλοντος μεταξύ παγκόσμιου ακαδημαϊκού ανταγωνισμού και Νέας Δημόσιας Διοίκησης - Giannakopoulos, Angelos; Maras, Konstadinos (My University, 2009)
The article seeks to analyse the Initiative of Excellence launched in German universities as of 2006 by mainly concentrating on the following fields: 1. while the problematic situation regarding opportunities of research offered to the main group of scientists working at German universities, namely to the group of postdoctoral scientists is described, the article asserts that 2. the criteria of evaluating excellence as such are not only vague but, moreover, have to be attached to an approach largely alien to scientific excellence itself. The article stresses that excellence is a precondition and at the same time the result of possessing social capital rather than the product of an objective set of evaluation criteria, fixed scales or quantitative stratification. The Initiative of Excellence aims at 3. modifying the traditional educational philosophy by replacing it with core aspects of the New Public Management consisting in the economic utilisation of research results, in reducing the costs of the administration and in rationalising the academic structures according to entrepreneurial principles. While all that results in serious questions vis-à-vis the vision of the university of the future, the article evaluates 4. respective institutional changes at the University of Excellence of Konstanz by stressing that all aforementioned points of critique coincide with the results of the evaluation at all levels.
The initiative of excellence in german universities : the academic vision of the future between global academic competition and new public management
The initiative of excellence in german universities : the academic vision of the future between global academic competition and new public management
Keywords: 300